Comprometimento organizacional: os impactos das percepções de cultura e suporte organizacionais - Oliveira, Beatriz de (2006)
The Organizational Commitment Construct has occupied a place of distinction in the field of research in Organizational behavior since the second half of the 1970´s. This relevance is justified by the interest of researchers in determining the precedents, correlates and consequences of such behavior and also through the interest of mangers on the their impact upon the Organizational context, when searching for ways to manage commitment of their employees using it as a differential in current competition However, research has pointed to gaps as to characteristics and organizational actions which trigger employee commitment to the organization. Therefore this study aimed to test a model that foresees perception of Organizational Support as a direct predecessor of the three components of Organizational Commitment Affectivity, Calculativity and Normativity - while perceptions of Organizational Culture would be indirect predecessors. Sample was composed of 202 employees, from different companies of diverse segments in the Triângulo Mineiro and region (state of Minas Gerais, Brasil) that voluntarily participated in the study. Data was obtained by applying the following scales: Club Culture Perception Scale, Culture of Function Perception Scale, Culture of Task Perception Scale, Culture Existence Perception Scale, Organizational Support Perception Scale, Affective Organizational Commitment Scale, Calculative Organizational Commitment Scale (evaluated by four factors Professional Losses, Investment Losses in the Organization, Organization Return Losses and Social Losses at Work) and Normative Organizational Commitment Scale. Twelve multiple analysis regressions were performed to test the model. The proposed model was confirmed only for Normative Organizational Commitment and for the Professional Losses factor of Calculative Organizational Commitment. Results revealed perceptions of Organizational Culture as direct predecessors of Affective Organizational Commitment. In relation to the rest of the Calculative Organizational Commitment factors (Investment Losses in the Organization, Organization Return Losses and Social Losses at Work) as independent variables were positioned on the same level. Next, multiple regressions were calculated stepwise to verify the best predictors of those criteria-variables of Organizational Commitment. Results showed that: perceptions of Cultural Existence and Club Culture were predictors of Organizational Commitment; Perceived Organizational Support was predictive of Normative Organizational Commitment and the Professional Losses factor of the Calculative Organizational Commitment; Perceived Organizational Support and Perceived Culture of Function were predictors of Organization Return Losses of the Calculative Organizational Commitment; the factors referring to Calculative Organizational Commitment - Investment Losses in the Organization and Social Losses at Work were mainly predicted by Perceived Organizational Support. These results were discussed, considering the impact of independent variables in explaining employee commitment to the company and an investigation agenda was proposed.